Effect of Different Coagulants and Various Concentrations on Quality of Jack Bean Tofu - Rini Yanti; Widiastuti Setyaningsih; Priyanto Triwitono; Richa Yuniansyah; Ermi Saraswati Maha Admi (Green Engineering Society, 2022)
Jack bean (Canavalia ensiformis), Indonesian local bean, has a high content of protein and great potential either for substituting or overcoming the shortage of imported soybean in tofu production. However, an appropriate coagulant in a proper amount is needed to make tofu with acceptable characteristics. This study set out to investigate the appropriate type and concentration of coagulant. The experiment was carried out by using GDL (glucono delta lactone) and nigari as coagulants with concentration levels of 0.25; 0.5; 0.75 and 1%. Some quality parameters such as yield, color, texture (hardness, cohesiveness, chewiness, springiness), and microscopic structure of tofu were observed. Consumer preference tests on aroma, color, taste, texture, and overall acceptability were directed to determine tofu with the best characteristics. The result showed nigari at concentration level 0.75% delivered the most preferred tofu for consumers.